Sociodemographic and regional differences in dietary climate impact: findings from Finnish population surveys - Sares-Jäske, Laura; Härkänen, Tommi; Tapanainen, Heli; Saarinen, Merja; Salminen, Jani; Valsta, Liisa; Paalanen, Laura (Frontiers Media S.A., 2025)
Introduction: Diet contributes substantially to one’s carbon footprint. Climate impact of diet varies between certain sociodemographic groups, but no studies have comprehensively compared the climate impact of diet between sociodemographic groups and regions in Finland. Aims of this study were to compare absolute and energy-adjusted dietary climate impacts between sociodemographic groups and to illustrate their regional distributions on maps. Methods: The FinHealth 2017 Study data (n = 5,123) comprising individuals aged 18–99 years, and additionally for the spatial analyses, FINRISK 2012 and Health 2011 survey data were utilized (combined n = 14,692). Dietary intake information was collected using validated food frequency questionnaires. Products’ climate impacts, produced with the life cycle assessment, were linked to the ingredient groups used in food consumption data, and individual-level climate impacts/day [kg CO2 equivalents (eq)/day and kg CO2 eq/megajoule/day] were estimated. Statistical analyses for maps were based on 10×10 km square data and on spatial Besag-York-Mollie model. Linear regression model was used to study differences between sociodemographic groups. Results and discussion: Men had higher absolute and energy-adjusted dietary climate impacts than women did. In women and in men, the climate impacts were the highest in the 35–54-year-olds, and those living with underage children, and the lowest in the 75–99-year-olds and those living alone. Women living in remote rural areas, and men in the highest income quintile had high dietary climate impacts. On maps, the climate impacts were low in southern Finland near the capital region. Higher levels appeared in men especially in parts of central Finland. Results of absolute and energy-adjusted climate impacts showed mainly similar patterns. Information on the differences between sociodemographic groups can be used when targeting policies concerning transition towards more climate-friendly diets to sociodemographic groups with high dietary climate impacts.
Keywords: climate impact of diet; greenhouse gas emissions; sociodemographic differences; regional distributions; distribution map